Cardiac autonomic responses induced by auditory stimulation with music is influenced by affinity - Plassa,Bruna de O. (2014)
INTRODUCTION: We aimed to evaluate the effects of musical auditory stimulation on cardiac autonomic regulation in subjects who enjoy and who do not enjoy the music. METHOD: The study was performed in young women (18-27 years old) divided in two groups (1) volunteers who enjoyed the music and (2) volunteers who did not enjoy the music. Linear indices of heart rate variability were analyzed in the time domain. The subjects were exposed to a musical piece (Pachelbel: Canon in D Major) during 10 minutes. Heart rate variability was analyzed at rest with no music and during musical auditory stimulation. RESULTS: In the group that enjoyed the music the standard deviation of normal-to-normal R-R intervals (SDNN) was significantly reduced during exposure to musical auditory stimulation. We found no significant changes for the other linear indices. The group composed of women who did not enjoy the music did not present significant cardiac autonomic responses during exposure to musical auditory stimulation. CONCLUSION: Women who enjoyed the music presented a significant cardiac autonomic response consisting of a reduction in heart rate variability induced by the musical auditory stimulation. Those who did not enjoy the musical piece presented no such response.